Inpatient treatment for severe obesity: A retrospective cohort study in Brazil, comparing exposure variables in a secondary data analysis - Domingos L. S. Rios; Márcia C. A. M. Oliveira; Sérgio Q. Braga; Matheus J. Chamorro; Beatriz L. B. Cunha; Ana C. R. Reis; Ana P. Guimarães; Ana D. N. Silva; Dandara A. R. Silva; Edilene M. Q. Araújo; Magno M. W. Pimentel (PLoS ONE, 2025)
Introduction: Very low-calorie diets with hospitalization have demonstrated promise as a viable therapeutic option for severe obesity and its associated comorbidities. However, large studies providing a comprehensive longitudinal observation of patients undergoing this therapy are lacking. We evaluated the effectiveness of treating severe obesity in hospitalized patients, using very low-calorie diets and clinical support to develop lifestyle changes. Methods: This study was a retrospective cohort comparing exposure variables in a secondary data analysis with a pre-post treatment design. Data were obtained from medical records of patients with severe obesity (grade II or III) treated in a Brazilian obesity specialist hospital from 2016 to 2022. The patients underwent a very low-calorie diet (500–800 kCal/day) and immersive changes in lifestyle habits, monitored by a multidisciplinary team. At 3 months, 777 patients presented complete data and 402 presented complete data at 6 months. The study compared changes in bioimpedance and laboratory tests, between men and women and age groups. Results: Three months of hospitalization yielded significant reductions in weight, body mass index (BMI), body fat, skeletal muscle mass, glucose, inflammatory, and lipid parameters. These reductions were more pronounced after 6 months, nearly doubling those observed at 3 months. In women, BMI and fat mass reduced by 10.4% and 15.2% at 3 months and 20.4% and 31.3% at 6 months, respectively. In men, BMI and fat mass decreased by 12.9% and 25.3 at 3 months and 23.6% and 45.3% at 6 months, respectively. Elderly individuals (aged ≥ 60 years) had smaller reductions in BMI and fat mass than non-elderly individuals (aged < 60 years) but still presented significant improvements. Conclusion: This study suggests the viability of treating severe obesity by hospitalization with low-calorie diets and immersive lifestyle changes. This treatment modality significantly improves anthropometric measurements, glucose, lipids, and inflammatory markers, thereby reducing cardiovascular risk.